ARWeld: Augmented Reality Mobile Learning Apps for Welding Technology - Amirah Binti Azlan, Elli; Khair Noordin, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The development of computer technology and multimedia software has made a lot of changes in the education world. Therefore, an application based on augmented reality technology has been developed for welding technology students, which is related to the topic of welding joints. The development of the ARWeld application was developed as an initiative to make the teaching and learning process easier for teachers and students. This ARWeld application was developed using AutoCAD 2017 and Unity 3D software as the main platform. Various types of graphic elements were combined in this application, such as text, animation, and 3D images. The main objective of this research is to design and develop a mobile application that uses augmented reality technology for welding technology. The prototype model has been used as a guideline in the making of the ARWeld application. It is hoped that this ARWeld mobile application will help welding technology students to make their learning process easier and more effective.